2015
DOI: 10.1097/fjc.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Boldine Ameliorates Vascular Oxidative Stress and Endothelial Dysfunction

Abstract: Abstract:Epidemiological and clinical studies have demonstrated that a growing list of natural products, as components of the daily diet or phytomedical preparations, are a rich source of antioxidants. Boldine [(S)-2,9-dihydroxy-1,10-dimethoxy-aporphine], an aporphine alkaloid, is a potent antioxidant found in the leaves and bark of the Chilean boldo tree. Boldine has been extensively reported as a potent “natural” antioxidant and possesses several health-promoting properties like anti-inflammatory, antitumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 108 publications
4
33
0
3
Order By: Relevance
“…However, we observed that the progression of the amyloid deposition is not modified by boldine treatment suggesting that if boldine has an effect on BBB, it is only marginal and likely not essential in its neuroprotective action. Second, boldine was also reported to have anti‐inflammatory effects (Lau et al, ), In agreement with this, we have shown that the level of TNFα was slightly but significantly reduced in APP/PS1 mice treated with boldine while IL‐1ß level was not significantly affected. We previously showed that inflammation is involved in Panx1 HC activitation in astrocytes close to amyloid plaques in APP/PS1 mice (Yi et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we observed that the progression of the amyloid deposition is not modified by boldine treatment suggesting that if boldine has an effect on BBB, it is only marginal and likely not essential in its neuroprotective action. Second, boldine was also reported to have anti‐inflammatory effects (Lau et al, ), In agreement with this, we have shown that the level of TNFα was slightly but significantly reduced in APP/PS1 mice treated with boldine while IL‐1ß level was not significantly affected. We previously showed that inflammation is involved in Panx1 HC activitation in astrocytes close to amyloid plaques in APP/PS1 mice (Yi et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…In this context, we have selected boldine, an alkaloid extracted from a Chilean tree, termed boldo. This molecule is known for its cytoprotective effects mostly mediated by its potent antioxidant properties reported in diverse i n vitro preparations as well as in animal models of diabetes, hypertension and atherosclerosis (Lau, Ling, Murugan, & Mustafa, ; O'Brien, Carrasco‐Pozo, & Speisky, ; Santanam Penumetcha, Speisky, & Parthasarathy, ). However, it was recently reported to block HCs and not gap junctions in mesangial cells in culture by a mechanism yet unknown but independent of its antioxidant property (Hernández‐Salinas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that hyperglycemia produces damaging effects through the overproduction of ROS or the impaired elimination by antioxidant enzymes, and are known to alter vascular functions (Johansen et al, 2005;Lau et al, 2014;Wong et al, 2013). To explore the protective mechanism of LMWF, the level of ROS, lipid peroxides Figure 3d,e).…”
Section: Lmwf Inhibited Oxidative Stress Via Regulation Of Antioxidanmentioning
confidence: 97%
“…Many previous studies have reported that DM is closely associated with vascular dysfunction via both endothelium‐dependent and ‐independent mechanisms . However, most studies of vascular dysfunction in diabetes have focused on the formation of reactive oxygen species (ROS), impairment of vasorelaxation, and abnormalities in vascular smooth muscle . Although several reports have revealed alterations in ion channel function during diabetes, studies of alterations in vascular voltage‐dependent K + (Kv) channel functions are limited …”
Section: Introductionmentioning
confidence: 99%